BODY IMAGE WITH EATING PATTERNS STUDENTS STIKES SANTA ELISABETH MEDAN - Nagoklan Simbolon; Pomarida Simbolon (JURNAL WIDYA MEDIKA, 2022)
Background: Students are individual figures who are in the process of changing from childhood to adulthood. These changes occur both physically, biologically as well as psychologically and socially. These physical changes depend on a person's diet which will build a body image or body image to a good or bad direction. This happened at STIKes Santa Elisabeth Medan, namely the eating pattern of 30% of STIKes students was not good. The purpose of the study was to determine the relationship between body image and diet in students at STIKes Santa Elisabeth Medan. Methods: the method used is descriptive analytic by using a cross sectional approach. The sample in this study amounted to 110 people with simple random sampling technique. Data analysis with chi-square test. Results: the results showed that the majority of respondents' body image was negative (71, 8%) and the majority of respondents' eating patterns are sufficient (54.6%). The results of the chi-square statistical test obtained p-value = 0.001 (p < 0.05), so there is a relationship between body image and diet in STIKes Santa Elisabeth Medan students. It is hoped that the campus will provide counseling to students so that body image is controlled.